A Poem that is Out of Plumb with Dr. Williams’ - Shapiro, Jerome F (Cornfield Review, 2021)
This poem, and the title, is an homage of William Carolos William's "This is Just to Say" (1934). What I find most interesting is my own mixed emotions, including embarassment, in response to what I have written.